Prevalence of sleep disorders in obese before bariatric surgery. - Carlos, Renata; Oliver, Nicole; Cruz, Ana Luísa F.; Silva, Suzanny Lays da; Souza, Jesimiel Missias de; Silva, Bruno Henrique F. da; Fialho, Davi; Bruno, Selma Sousa (Manual Therapy, Posturology & Rehabilitation Journal, 2017)
Introduction: The prevalence of sleep disorders (SD) has increased significantly in recent decades in parallel to the worldwide obesity epidemic. The presence of SD provides an increased risk of postoperative complications, requiring greater care in these patients. The gold standard for evaluation and diagnosis of SD is polysomnography, but it is an expensive and highly complex exam, making the questionnaires and scales more accessible for diagnosis and screening. Objectives: To evaluate the presence of SD and to analyze the influence of anthropometric measures on the scores of the Epworth Sleepiness Scale (ESS), snoring (ERS) and Stanford Sleepiness Scale (SSS) in obese patients. Method: An observational, cross-sectional study performed from August 2015 to August 2016. The patients in the preoperative group of bariatric surgery of the University Hospital were submitted to anthropometric evaluation and application of the ESS, ERS and SSS during the preoperative physiotherapy evaluation. Results: Were evaluated 100 obese (78 women), mean age of 41.4±10.7 years and BMI of 46.1±7.8kg/m2 . SD were identified in 25% by ESS and 21% by SSS of obese. There were no differences between genders for the scales scores. The score of the ERS correlated itself with waist (r=0.20, p=0.04) and neck (r=0.33, p=0.001) circumferences. Conclusion: The use of scales for diagnosis of SD is useful in the follow-up of the preoperative of bariatric surgery and our study found that 25% of patients present daytime somnolence. We also observed the influence of waist and neck circumferences on increasing snoring scale.